Continuity of care and health care cost among community‐dwelling older adult veterans living with dementia. (19th August 2020) - Lei, Lianlian; Intrator, Orna; Conwell, Yeates; Fortinsky, Richard H.; Cai, Shubing
Abstract: Objectives: To estimate the causal impact of continuity of care (COC) on total, institutional, and noninstitutional cost among community‐dwelling older veterans with dementia. Data Sources: Combined Veterans Health Administration (VHA) and Medicare data in Fiscal Years (FYs) 2014‐2015. Study Design: FY 2014 COC was measured by the Bice‐Boxerman Continuity of Care (BBC) index on a 0‐1 scale. FY 2015 total combined VHA and Medicare cost, institutional cost of acute inpatient, emergency department [ED], long‐/short‐stay nursing home, and noninstitutional long‐term care (LTC) cost for medical (like skilled‐) and social (like unskilled‐) services were assessed controlling for covariates. An instrumental variable for COC (change of residence by more than 10 miles) was used to account for unobserved health confounders. Data Collection: Community‐dwelling veterans with dementia aged 66 and older, enrolled in Traditional Medicare ( N  = 102 073). Principal Findings: Mean BBC in FY 2014 was 0.32; mean total cost in FY 2015 was $35 425. A 0.1 higher BBC resulted in (a) $4045 lower total cost; (b) $1597 lower acute inpatient cost, $119 lower ED cost, $4368 lower long‐stay nursing home cost; (c) $402 higher noninstitutional medical LTC and $764 higher noninstitutional social LTC cost. BBC had no impact on short‐stay nursing home cost. Conclusions: COC is an effective approach to reducing total health care cost by supporting noninstitutional care and reducing institutional care.